A break in cultural legacy: child grave inventories from Tell Arbid, Syria, in transition from EBA to MBA. (2nd September 2018) - Wygnańska, Zuzanna
Abstract : The cultural and occupational continuity between Early and Middle Bronze Ages in the Upper Khabur basin, north-eastern Syria has been investigated before with regard to pottery and settlement patterns. This paper addresses the question from the less commonly explored perspective of funerary behaviour and, in particular, material culture represented by grave finds from Tell Arbid in Syria. Material from five child graves dated to the late 3rd millennium BC, presented in this paper, and complementary data on other child graves from the region, provide grounds for discussion. This touches specifically upon jewellery placed in graves. Personal adornments from the late EBA child graves display a strong cultural affinity with those of the 3rd millennium BC, and are indicative of a distinctive social identity for their users. This differs from that of the population that continued to use the same burial ground in the early 2nd millennium BC. The material provides a thought-provoking case for recognizing a break in the cultural legacy between the EBA and MBA despite possible continuity in settlement. Adult burials from the period, which are fewer and mostly devoid of grave goods other than pottery, are largely excluded from the discussion as they do not contribute so effectively to our understanding of these changes.